Proceedings of the 9th Annual Conference on Genetic and Evolutionary Computation 2007
DOI: 10.1145/1276958.1277193
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithms for large join query optimization

Abstract: Genetic algorithms (GAs) have long been used for large join query optimization (LJQO). Previous work takes all queries as based on one granularity to optimize GAs and compares their efficiency with other query optimization algorithms. However, we believe that large join queries are based on a granularity that is too large (1) to optimize GAs and (2) to compare the efficiency of different randomized optimization algorithms. Besides, while previous work only discusses the efficiency of basic GAs for LJQO, we bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 6 publications
0
36
0
Order By: Relevance
“…According to the commutative, equivalence and associative rules for the join operators, the logical optimizer generates firstly many different join trees, each of them is equivalent to the given query graph. For that such join tree, every base relation is represented by a leaf and the results of the join operation is represented by an inner node [3]. The assessment criteria of the logical optimizer depends mainly on the total cost of join operations included in any query access plan alternative.…”
Section: Optimization Processmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the commutative, equivalence and associative rules for the join operators, the logical optimizer generates firstly many different join trees, each of them is equivalent to the given query graph. For that such join tree, every base relation is represented by a leaf and the results of the join operation is represented by an inner node [3]. The assessment criteria of the logical optimizer depends mainly on the total cost of join operations included in any query access plan alternative.…”
Section: Optimization Processmentioning
confidence: 99%
“…Those factors include: (a) The number of base relations, (b) the equivalent join tree, (c) the expected cardinality of each involved relation, and (d) the expected occurrence for each distinct value of the involved relations' attributes [3]. Some of these factors are known a priori, such as the number of involved relations and the structure of the join tree.…”
Section: The Proposed Cost Modelmentioning
confidence: 99%
“…Firstly, it generates a set of candidate query access plans represented as join trees or query graphs. In each join tree, each relation is represented by a leaf node and each join operation is represented by an inner node [2]. Consequently, the logical optimizer starts evaluating each candidate query access plan respecting the total cost of the involved join operations.…”
Section: Optimization Processmentioning
confidence: 99%
“…Those factors include: (a) The number of base relations, (b) the equivalent join tree, (c) the expected cardinality of each involved relation, and (d) the expected occurrence for each distinct value of the involved relations' attributes [2]. Some of these factors are known a priori such as the number of involved relations and the structure of the join tree.…”
Section: The Cost Model Of the Proposed Approachmentioning
confidence: 99%
“…The authors showed clear advantages of randomized algorithms to choose good plans. In addition, others works can be mentioned describing the quality of such algorithms [4], [5], [7], [8]. In spite of the good results demonstrated by randomized algorithms, these works present as result, the average cost or the best costs obtained by these algorithms.…”
Section: Introductionmentioning
confidence: 99%